Enhancing Quality of Life in Multiple Sclerosis Patients through Personalized (Temperament-Based) Traditional Persian Medicine: An Investigation into the Efficacy of Lifestyle Education (Non-Randomized Pretest-Posttest Study) - Ali Akhondpour Manteghi; Amir Broumand; Farzad Goli; Mohammad Reza Noras (Traditional and Integrative Medicine)
Multiple sclerosis (MS) profoundly affects patients' well-being, causing physical and psychological challenges. While lifestyle factors are recognized as pivotal in MS management, research on traditional Persian (Iranian) medicine approaches remains scarce. This study aimed to assess the efficacy of temperament-based lifestyle education rooted in Persian medicine principles in ameliorating quality of life (QoL) among MS patients. Employing a pretest-posttest quasi-experimental design, we enrolled 30 female MS patients, randomly assigned to either an experimental group receiving tailored lifestyle interventions or a control group. QoL assessments were conducted pre-intervention, post-intervention, and at a one-month follow-up. The intervention spanned four weeks, focusing on individualized nutrition, exercise, sleep optimization, stress management, and socio-emotional well-being, aligned with each participant's temperament profile. The Covariance analysis exhibited significantly greater enhancements in post-intervention and follow-up QoL scores compared to controls, with effect sizes indicating substantial impact. Notably, these improvements were sustained at the one-month follow-up assessment. Our findings suggest that temperament-based lifestyle education grounded in Persian medicine holds promise as a beneficial and low-risk strategy for enhancing QoL in MS patients (51.93 to 72.86 increased). Further validation through larger randomized trials is warranted, yet this preliminary investigation underscores the potential of integrative approaches leveraging traditional medical paradigms.